2013
DOI: 10.2528/pier12080808
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Magnetic-Geared Permanent-Magnet Machines

Abstract: Abstract-With the advent of magnetic gears, researchers have developed a new breed of permanent-magnet machines. These magnetic-geared permanent-magnet machines artfully incorporate the concept of magnetic gearing into the permanent-magnet machines, leading to achieve low-speed high-torque direct-drive operation. In this paper, a quantitative comparison of three viable magnetic-geared permanent-magnet machines is firstly performed, hence revealing their key features, merits, demerits and applications.Initially… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(45 citation statements)
references
References 52 publications
0
45
0
Order By: Relevance
“…Compared to the mechanical gear, the torque transmission of the magnetic gear has no contact, thus avoiding any abrasion of the in-contact parts or mechanical noise. Additionally, the magnetic gear itself has overload protection ability [49]. Figure 14a shows the basic structure of a coaxial magnetic gear.…”
Section: Magnetic-geared In-wheel Drive Systemmentioning
confidence: 99%
“…Compared to the mechanical gear, the torque transmission of the magnetic gear has no contact, thus avoiding any abrasion of the in-contact parts or mechanical noise. Additionally, the magnetic gear itself has overload protection ability [49]. Figure 14a shows the basic structure of a coaxial magnetic gear.…”
Section: Magnetic-geared In-wheel Drive Systemmentioning
confidence: 99%
“…Ferromagnetic material provides modulation (changing) of the magnetic field. This concept of transmission is patented by Martin [22], however, its performances, especially high magnetic density, are more discussed in the papers [23,24]. The inner rotor is usually the rotor of the higher speed rotation, and outer rotor is the rotor of the lower speed rotation.…”
Section: Types Of Magnetic Gearsmentioning
confidence: 99%
“…The inner rotor is usually the rotor of the higher speed rotation, and outer rotor is the rotor of the lower speed rotation. Figure 4 Field-modulated magnetic gears a) Linear magnetic gear [25], b) Axial magnetic gear [21], c) Coaxial magnetic gear (CMG) [23] Comparative characteristics of mechanical and magnetic gears are given in Table 1. Some of the advantages of magnetic gears are that there are no noise and vibrations, no contact, so therefore, there is no need to use a lubricant.…”
Section: Types Of Magnetic Gearsmentioning
confidence: 99%
“…Research and development in magnetic gearing has attracted a lot of interest recently because of its potential for efficient transmission torque, lubrication free maintenance, overload protection and noncontact operation compared to mechanical gears that have problems of friction, wear and tear [1]. References [2,3] reported that by integrating a magnetic gear with a PM machine, the resultant magnetic geared machine can be used as generators in low-speed renewable energy power generation applications.…”
Section: Introductionmentioning
confidence: 99%